An Empirically Based Theory of the Relationships among Social Embeddedness, Economic Viability, Learned Recovery Skills and Perceived Quality of Life in Recovery Homes. Issue 1 (2nd January 2020) - Jason, Leonard A.; Stevens, Edward B.; Light, John M.; Doogan, Nathan J.
ABSTRACT: Key characteristics of recovery homes include governance style (which can play a central role in structuring recovery mechanisms), social embeddedness (e.g., social relationships within the home), economic viability (e.g., the individual's ability to be self-supporting), and learned recovery skills (such as coping with stress, avoiding putting one's self in risky situations, etc.). These domains can have important associations with perceived quality of life (measured across physical, psychological, social relationships, and environmental domains). The current study investigated relationships among these key "active ingredients" of recovery homes. In addition, we present a dynamic model consistent with these observed relationships, to illustrate how relevant mechanisms interact over time and affect system evolution. Data were collected from recovery home residents in three states. Findings supported our overall hypotheses, indicating that social embeddedness, stress, and self-efficacy were related to quality of life, and policy and treatment-design implications are further examined by simulating system dynamics.